A subset of high Gleason grade prostate carcinomas contain a large burden of prostate cancer syndecan‐1 positive stromal cells. Issue 13 (26th July 2017) - Sharpe, Benjamin; Alghezi, Dhafer A.; Cattermole, Claire; Beresford, Mark; Bowen, Rebecca; Mitchard, John; Chalmers, Andrew D.
Abstract : Background: There is a pressing need to identify prognostic and predictive biomarkers for prostate cancer to aid treatment decisions in both early and advanced disease settings. Syndecan‐1, a heparan sulfate proteoglycan, has been previously identified as a potential prognostic biomarker by multiple studies at the tissue and serum level. However, other studies have questioned its utility. Methods: Anti‐Syndecan‐1 immunohistochemistry was carried out on 157 prostate tissue samples (including cancerous, adjacent normal tissue, and non‐diseased prostate) from three independent cohorts of patients. A population of Syndecan‐1 positive stromal cells was identified and the number and morphological parameters of these cells quantified. The identity of the Syndecan‐1‐positive stromal cells was assessed by multiplex immunofluorescence using a range of common cell lineage markers. Finally, the burden of Syndecan‐1 positive stromal cells was tested for association with clinical parameters. Results: We identified a previously unreported cell type which is marked by Syndecan‐1 expression and is found in the stroma of prostate tumors and adjacent normal tissue but not in non‐diseased prostate. We call these cells Prostate Cancer Syndecan‐1 Positive (PCSP) cells. Immunofluorescence analysis revealed that the PCSP cell population did not co‐stain with markers of common prostate epithelial, stromal, or immune cell populations. However, morphological analysis revealed that PCSP cells are often elongated and displayed prominent lamellipodia, suggesting they are an unidentified migratory cell population. Analysis of clinical parameters showed that PCSP cells were found with a frequency of 20‐35% of all tumors evaluated, but were not present in non‐diseased normal tissue. Interestingly, a subset of primary Gleason 5 prostate tumors had a high burden of PCSP cells. Conclusions: The current study identifies PCSP cells as a novel, potentially migratory cell type, which is marked by Syndecan‐1 expression and is found in the stroma of prostate carcinomas, adjacent normal tissue, but not in non‐diseased prostate. A subset of poor prognosis high Gleason grade 5 tumors had a particularly high PCSP cell burden, suggesting an association between this unidentified cell type and tumor aggressiveness.